Photostable organic solar cells based on non-fullerene acceptors with an aminated bathocuproine electron transport layer. Issue 9 (20th February 2023) - Kim, Yong Ryun; Lee, Sanseong; Kim, Juae; Oh, Juhui; Kim, Ju-Hyeon; Ki, Taeyoon; Oh, Chang-Mok; Hwang, In-Wook; Suh, Hongsuk; Lee, Kwanghee; Kim, Heejoo
Abstract : Solution-processed bathocuproine (BCP) has been widely used in fullerene (FA)-based organic solar cells (OSCs) for decades as an electron transport layer (ETL). Abstract : Solution-processed bathocuproine (BCP) has been widely used in fullerene (FA)-based organic solar cells (OSCs) for decades as an electron transport layer (ETL). However, it has not emerged for use in non-fullerene acceptor (NFA)-based OSCs due to the interfacial chemical interaction between the NFA and BCP, leading to poor device performance. Herein, newly synthesized amine-functionalized bathocuproine (BCPN) is successfully applied as an electron transport layer (ETL) in NFA based OSCs (PM6:Y6 and PM6:BTP-ec9) for the first time with a power conversion efficiency (PCE) of 15.5% and 16.7%, respectively. Nonencapsulated OSCs based on PM6:Y6 and PM6:BTP-ec9 built using BCPN demonstrate substantially improved photostability ( T 80 ∼ 140 and 100 hours, respectively) compared to both control devices built using BCP ( T 80 ∼ 1 hour) under continuous photoirradiation (AM 1.5 G, 100 mW cm −2 ). The improvement in photostability is primarily attributed to the prevention of the breakage of the conjugated bond in the NFAs (Y6 and BTP-eC9). This is verified by the observation that the surface morphology of BCPN on the bulk-heterojunction (BHJ) layer is retained, whereas that of BCP on the BHJ layer is completely degraded, leading to an inferior photostability for OSCs. Moreover, we further explored the behaviour of charge extraction property in the NFA based OSCs built using BCPN and BCP as a function of photoirradiation time. It also preserves the charge extraction property in the NFA based OSCs built using BCPN. Thus, our approach demonstrates that the amination of the BCP moiety (BCPN) affords a desirable ETL material for improving the photostability of OSCs based on NFAs without sacrificing the PCE.